TEACHERS’ REASON TO ENGAGE STUDENTS IN LEARNING DESCRIPTIVE TEXT THROUGH ONLINE - Nenglis Lumban Gaol; Berlin . Sibarani; Rahmad . Husein (LINGUISTIK TERAPAN, 2022)
ABSTRACTOnline learning is learning that takes place over the Internet. It uses electronic media (usually a computer) for a variety of learning purposes to access the learning materials and to interact with the teacher and with other students. Furthermore, students’ engagement in online learning is very important because online learners seem to have fewer opportunities to be engaged with the institution. Hence, it is essential to create multiple opportunities for student engagement in the online environment. The objective of this study is to elaborate the reasons in engaging students to learn descriptive text through online learning. This study was conducted at grade VII of Junior High School students. A qualitative descriptive research design was applied and the data gathered from the sentences of teacher and students during online learning and when teacher was interviewed. This study followed the theory of Kuh (2009) about the reasons of engaging students during the learning through online learning. Furthermore, the result of the study showed that there were two reasons of engaging the students in learning descriptive through online; they were: 1) the engagement contributes students' better understanding and 2) the engagement is needed for cognitive development.